Etiology of Inguinal Hernias: A Comprehensive Review - Öberg, Stina; Andresen, Kristoffer; Rosenberg, Jacob (Frontiers in Surgery, 2017)
Background: The etiology of inguinal hernias remains uncertain even though the lifetime risk of developing an inguinal hernia is 27% for men and 3% for women. The aim was to summarize the evidence on hernia etiology, with focus on differences between lateral and medial hernias. Results: Lateral and medial hernias seem to have common as well as different etiologies. A patent processus vaginalis and increased cumulative mechanical exposure are risk factors for lateral hernias. Patients with medial hernias seem to have a more profoundly altered connective tissue architecture and homeostasis compared with patients with lateral hernias. However, connective tissue alteration may play a role in development of both subtypes. Inguinal hernias have a hereditary component with a complex inheritance pattern, and inguinal hernia susceptible genes have been identified that also are involved in connective tissue homeostasis. Conclusions: The etiology of lateral and medial hernias are at least partly different, but the final explanations are still lacking on certain areas. Further investigations of inguinal hernia genes may explain the altered connective tissue observed in patients with inguinal hernias. The precise mechanisms why processus vaginalis fails to obliterate in certain patients should also be clarified. Not all patients with a patent processus vaginalis develop a lateral hernia, but increased intraabdominal pressure appears to be a contributing factor.